Pengaruh Pendapatan Asli Daerah Terhadap Kinerja Keuangan Pemerintah Daerah: Studi Empiris pada Kabupaten/Kota di Provinsi Jawa Tengah - Skolastika Bunga Aryani; Cahyani Nuswandari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze and examine the effect of local revenue—comprising local taxes, regional levies, separated regional wealth management results, and other legitimate local revenues—on the financial performance of local governments, as measured by the regional financial independence ratio. The research utilizes secondary data in the form of panel data obtained from the Budget Realization Reports of 35 regencies/cities in Central Java Province for the 2020–2024 period. The entire population was included in the sample, utilizing a census method for data collection. Research data were analyzed using the panel data regression technique. The results indicate that local taxes, regional levies, separated regional wealth management results, and other legitimate local revenues have a positive and significant effect on local government financial performance. These findings demonstrate that the optimization of all local revenue components is directly proportional to the improvement of local government financial performance.